2003
DOI: 10.1021/la0203741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening of Intermicellar Interactions on the Linear and Nonlinear Rheology of a Viscoelastic Gel

Abstract: We report our studies of the linear and nonlinear rheology of aqueous solutions of the surfactant cetyl trimethylammonium tosylate (CTAT) with varying amounts of sodium chloride (NaCl). The CTAT concentration is fixed at 42mM and the salt concentration is varied between 0mM to 120mM. On increasing the salt (NaCl) concentration, we see three distinct regimes in the zero-shear viscosity and the high frequency plateau modulus data. In regime I, the zero-shear viscosity shows a weak increase with salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
(109 reference statements)
2
27
0
Order By: Relevance
“…The value of α in the Cole-Davidson model [16] gives an estimate of the width of the distribution of relaxation times. Multiexponential relaxation processes are seen in dilute micellar solutions where α < 1, with α increasing to 1 with increasing surfactant and/or salt concentrations [23,24]. On adding SiO 2 to semidilute aqueous solutions of CTAT, we find a similar increase in the values of α suggesting an approach towards single exponential stress relaxation.…”
Section: Discussionmentioning
confidence: 56%
“…The value of α in the Cole-Davidson model [16] gives an estimate of the width of the distribution of relaxation times. Multiexponential relaxation processes are seen in dilute micellar solutions where α < 1, with α increasing to 1 with increasing surfactant and/or salt concentrations [23,24]. On adding SiO 2 to semidilute aqueous solutions of CTAT, we find a similar increase in the values of α suggesting an approach towards single exponential stress relaxation.…”
Section: Discussionmentioning
confidence: 56%
“…External stimuli such as light and temperature are found to tune the size and shape of selfassembling molecules and thereby control their assembly in solution [5,6]. The flow behavior of surfactant solutions have been studied extensively, both theoretically and experimentally [7,8]. In aqueous cetyl trimethyl ammonium bromide (CTAB) thread-like micelles appear above 11 wt.% and form an isotropic phase at 27°C.…”
Section: Introductionmentioning
confidence: 99%
“…Their d-JS-φ model (spatially non-local Johnson-Segalman model with concentration coupling) calculations predict a positive value for the slope of the plateau in the banded region of the flow curve, and the slope increases with the strength of the coupling between flow and concentration fluctuations ( figure 4). In a recent experimental work, Bandyopadhyay and Sood [27] have shown that the slope α of the stress plateau, which we find is a power law σ ∼ γ α , for worm-like micellar solutions of surfactant cetyltrimethylammonium tosylate (CTAT) can be tuned by adding salt (NaCl) ( figure 5).…”
Section: Motivationmentioning
confidence: 72%